Programming with constraints : an introduction - Marriott, Kim (MIT Press, 1998)
The job of the constraint programmer is to use mathematical constraints to model real world constraints and objects. In this book, Kim Marriott and Peter Stuckey provide the first comprehensive introduction to the discipline of constraint programming and, in particular, constraint logic programming. The book covers the necessary background material from artificial intelligence, logic programming, operations research, and mathematical programming. Topics discussed range from constraint-solving techniques to programming methodologies for constraint programming languages. Because there is not yet a universally used syntax for constraint logic programming languages, the authors present the programs in a way that is independent of any existing programming language. Practical exercises cover how to use the book with a number of existing constraint languages.